P17.01 Performance evaluation of the genexpert hiv-1 quant assay for detection of hiv-1 in plasma. (13th September 2015) - McNally, L; Carrera, A; Sherring, J; Cunningham, PH
Abstract : Introduction: The HIV-1 Quant Assay performed on the GeneXpert® Instrument Systems, is designed for the rapid quantitation of HIV-1 in human plasma with an analytical range of 40 to 10, 000, 000 copies/mL for HIV-1 Group M subtypes A, C, D, AE, F, G, H, AB, AG, J, K and Groups N and O. Testing is performed in a single-use disposable GeneXpert cartridges that hold the real-time reverse transcriptase polymerase chain reaction (RT-PCR) reagents and host the RT-PCR processes. This study assessed the performance of the system in routine plasma. Methods: To date, a total of 130 plasma samples have been tested over the analytical range and compared to a benchmark real time PCR system. Seventy four samples (56.9%) were of a known subtype comprising of subtype B (37.6%), AE (7.7%), C (4.6%) AG (1.5%) and mixed (4.6%). Additional samples consisting of an external quality control samples run over multiple days, and samples with HIV-1 RNA not detected or below the lower limit of were also tested to assess performance. Results: Overall the HIV-1 Quant Assay performed on the GeneXpert® Instrument Systems correlated with the routine analytical platform (r2 = 0.9333). Samples ranged undetectable (16, 8.8%), below the benchmark test lower limit of detection (<20 cpy/ml) (10, 7.9%), low range (20–5, 000) (43, 33.1%), medium (5, 000–50, 000) (24, 18.5%) and high range (>50, 000 cpy/ml) (29, 22.3%). Thirteen samples (10%) were invalid as a result of insufficient sample. Samples in the lower analytical range <1, 000 cpy/ml showed little variance when compared with the Roche (CAP/CTM) assay using Bland-Altman correlation analysis. Reproducibility was assessed in the high, medium and low range within 1–2SD of mean. Sixteen replicates of a commercial external control showed very good reproducibility. Conclusion: The HIV-1 Quant Assay performed on the GeneXpert® Instrument Systems correlated with a commonly used HIV RNA test in plasma and offered significant workflow advantages. The system has a small footprint and requires no further consumables other that the single-use test cartridges. Further studies are planned to fully assess the assay performance. Disclosure of interest statement: No conflict of interest to declare.